Updating NAMOD: A Namibian tax-benefit microsimulation model - Gemma Clare Wright; Michael Noble; Helen Barnes; David McLennan; Michell Mpike (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
This paper provides an account of a Nambian tax-benefit microsimulation model - NAMOD - which has been developed for use by government. Following a section on the importance of social security in Namibia and recent related studies, the paper outlines the tax-benefit policies that are included within NAMOD and describes the data challenges and assumptions that had to be made in order to simulate these policies. Results for 2015 are compared with reported administrative data. In spite of current data challenges, NAMOD can be used to help inform social security policy design.
Keywords: C63; H24; I38; 330; tax-benefit; microsimulation; South Africa